Study of annealing effects on the physical properties of evaporated SnS thin films for photovoltaic applications - Tariq, G. H.; Hutchings, K.; Asghar, G.; Lane, David W.; Anis-Ur-Rehman, M. (Cranfield University, 2014)
Tin Sulphide (SnS) thin films have been deposited on glass slides by thermal evaporation using SnS powder. The improvements in the structural and optical properties of SnS thin films on annealing at different temperatures (200 degrees C, 300 degrees C, 400 degrees C, and 500 degrees C) in vacuum for one hour are presented in this work. The thin films annealed at 500 degrees C were decomposed, which limits the annealing temperature below than 500 degrees C. X-ray diffraction characterization showed an intensive peak at 31.8 degrees originating from (111) reflection. Ellipsometry measurements were done for optical studies and optical absorption coefficient for as-deposited films was 2.02 x 10(4) increased to 4.90 x 10(4) (cm)(-1) for films annealed to 300 degrees C for incident photon energies 1.55eV, and direct band gap of 1.90 eV was indicated.
Keywords: SnS; Thermal evaporation; Ceramic crucible; Absorption coefficient; Band gap